Pengaruh Penggunaan Worksheet Materi Asam Basa Berbasis Kearifan Lokal terhadap Hasil Belajar Siswa - Isdayanti Isdayanti; Ardian Trio Wicaksono; Helda Rahmawati (Al Kawnu : Science and Local Wisdom Journal, 2022)
This research is to see the effect of using local wisdom-based acid-base worksheets on student learning outcomes using a quantitative approach with the type of research research experiment. The design used was pretest-posttest control group design. Sampling using purposive sampling technique. The samples were students of class XI MIA 3 (control class) and students of class XI MIA 4 (experimental class) at SMAN 9 Banjarmasin. The calculation steps of the research use SPSS 22 for windows. The data processing technique used independent sample t-test to test the difference between pretest and posttest. The results of the analysis of the data obtained, independent sample t-test test showed that there was no difference between the SPSS pretest output of the control and experimental classes, the SPSS posttest output between the control and experimental classes was different. Test the hypothesis using the N-Gain score test. The results of the SPSS output test N-Gain score, the mean value of the control class is in the medium category, while the mean output of the experimental class shows the Gain score in the high category. The use of local wisdom based acid base worksheets in the experimental class has a high effect on student learning outcomes.